Regionalização climática e projeções da produção per capita de lavouras alimentares de sequeiro no estado do Maranhão - Sousa, Erika Costa (2023)
The state of Maranhão has a better rainfall regime than other states in the Northeast, but there are irregularities in the spatial and temporal rainfall distribution, which results in serious problems in the development of crops, with economic and social impacts. Rice, bean, cassava and corn crops play an important role in shaping food security, generating income and occupation of the farmers, who are mostly family farmers. However, these crops are subject to variations in the availability and regularity of rainfall, precisely because they are dryland. For having a huge territory and presenting Cerrados, Caatinga and Amazon biomes, the climatic regime and the agricultural aptitude of the state must vary in different geographic spaces. The present study has the following objectives: a) To classify rainfall in Maranhão between the years 1901 and 2020 into periods: Scarce; Normal; and Rainy; b) To evaluate whether the climatic regions created for the state present differences in their respective rainfall averages, considering the series of rainfall observed between the years 1901 and 2020; c) To evaluate the instability of the annual rainfall of Maranhão between the years 1901 and 2020 with unfolding for the 10 climatic sub-regions in which the state was divided; d) Make projections of the trajectory of the aggregate per capita production, productivity and harvested area of rice, beans, cassava and corn between 1933 and 2021; e) Assess whether the aggregate per capita production of these crops was sustainable throughout the evaluation period. The research used secondary data from Produção Agrícola Municipal (PAM), Anuários estatísticos do IBGE, and climatic data from the National Oceanic and Atmospheric Administration (NOAA, USA) database. The methodologies used include descriptive statistical analyses of the variables related to rice, bean, cassava and corn productions, as well as of the rainfall observed in the municipalities and in the state. In addition, factor analyses were applied to aggregate the variables that define crop yields. To study the trajectory of the per capita production of food in aggregate form, the ARIMA model was used, which was also employed to make forecasts until the year 2031 of the per capita production of food in the state, considering different population growth scenarios for this period. The research estimated the continuous geometric growth rates (GCGR), at different stages of the per capita food production trajectory. The results showed that the average rainfall for the state in these 120 years was 1,624.78 mm, with a coefficient of variation of 17.42%. The air temperature showed homogeneous distribution, without great oscillations, having a minimum of 26.03 °C, a maximum of 28.76 and an average of 27.18 °C. In relation to the rainy periods, 30 years of scarcity, 57 years of normality and 33 rainy years were identified. The average per capita production of the crops showed heterogeneous behavior, with considerable peaks and troughs,being better in the rainy periods and worse in the lean years. The work was able to answer the questions, considering that ten climatic regions that have different average rainfall. However, the agricultural productions of these regions aggregated into the productivity index, created using the factor analysis method, were not all statistically different. The TGC calculated for two periods of the trajectory of per capita production of the crops studied was positive between 1933 and 1982 and negative from 1983 onwards, with a smaller magnitude than that estimated for the previous period. Thus, the work concludes that there is a period in which the per capita production of crops was sustainable (1933 to 1982) and another in which this did not happen (1982 to 2020).